Sosialisasi Model “Fun with English” dengan Menggunakan Metode Game Based Learning dalam Melatih Kemampuan Pronounciation Siswa di SMP Negeri 3 Pematangsiantar - Silaban, Gabriella Clarisa; Purba, Igna Mariana; Sirait, Eka Uchi Monica; Marbun, Elisa May Yolanda; Purba, Indra Pranata; Siagian, Claudya Benesa; Panjaitan, Anita; Herman, Herman; Sibarani, Imelda Sabrina; Sinurat, Bloner (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this outreach program is to provide insight and knowledge in English to students. The socialization activity, which was attended by 32 students, took place at SMP Negeri 3 Jalan Lagu Boti Ujung Pematangsiantar on May 17, 2023. This socialization was carried out using the game-based learning method and also discussed various problems in learning English that are often faced by students. The result of the implementation of this activity is that students become motivated to learn English through discussion after the presentation of the material is finished. From these socialization activities, the researcher concluded that students were able to learn English in a fun way according to the topics that had been presented.